Impact of Naoh Modification on the Cellulosic Content of Anthracothorax Viridis Mango Wood Fiber (AVMWF) for Component of Polymer Composite - Government Rabonni Mike; Odiakaose Chili; Nweke Onyeka Christian (SEAN Institute, 2025)
his research investigated how alkali treatment affects the chemical composition of Anthracothorax Viridis mango wood fiber (AVMWF). The study, conducted on samples from Kinkiso in Taraba State, Nigeria, sought to understand how soaking AVMWF powder in various concentrations of NaOH for different durations would alter its cellulose, hemicellulose, and lignin content. The initial chemical composition of the untreated AVMWF was 38.75% cellulose, 29.89% hemicellulose, and 30.28% lignin. The study found that alkali treatment significantly altered these percentages. The most notable result was a dramatic increase in cellulose content to 70.45%. This was achieved after soaking the AVMWF in a 7.6% (w/v) NaOH solution for 3.2 hours. Under these same conditions, the hemicellulose and lignin content were significantly reduced to 17.91% and 10.64%, respectively. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed the chemical changes. The FTIR spectrum showed that the treated and untreated AVMWF had variant functional groups, specifically confirming changes in the hydroxyl (OH), carboxyl (COOH), carbon-hydrogen (C-H), and carbonyl (C=O) bonds. These spectroscopic results support the conclusion that the NaOH treatment successfully modified the fiber's chemical structure. The findings demonstrate that treating AVMWF with NaOH effectively increases its cellulose content while reducing its hemicellulose and lignin. Because of its new properties, which are similar to other natural fibers used in manufacturing, the study recommends that AVMWF be explored for its potential use in composite material production.